The The Effectiveness of Public Services by the Indonesian National Police in Enhancing the Security of Vital Objects in Manado City - Carlos, Yosua Eurico Warenstein; Niode, Burhan; Waworundeng, Welly (Journal of Public Administration and Government, 2023)
This research discusses the role of the Indonesian National Police in ensuring the security of vital objects in the city of Manado. The aim is to evaluate the effectiveness of public services provided by Indonesian National Police in achieving optimal security levels for these vital objects. The research employs data analysis methods, literature review, as well as surveys and interviews with relevant stakeholders. The research findings indicate that, despite Indonesian National Police's efforts to enhance the security of vital objects, there are still obstacles in the effectiveness of public services, including resource limitations and a lack of inter-agency coordination. Therefore, improvement efforts are needed in management, resource enhancement, and better cooperation among relevant stakeholders. The conclusion of this research is that the effectiveness of Indonesian National Police's public services plays a crucial role in achieving optimal security for vital objects in the city of Manado, and improvements are required to address the existing challenges.